A.I. in Islam: The Crossroad of A.I. and Islamic Teachings - Zakariah, Helmi (International Journal of Human and Health Sciences (IJHHS), 2019)
Mankind in its historical narrative – almost always immodestly regards itself as the most intelligent among all God’s creation. Either through a self – label of “Homo Sapiens” (the wise men) or the dogma of being the Khalifah (leader) of the earth. But what does it mean by intelligence? What is the epistemology (origin) of our collective knowledge? And does it bring us closer to wisdom? These points that we commonly take for granted, must be examined continuously in our trending pursuit of translating (or, imposing) our thinking architecture to machine learning and Artificial Intelligence. From the origin of the commonly-used term “algorithm” in A.I. (spoiler: it was originally coined by a Muslim mathematician of the 9th century, of a similar-sounding name) to the interjunction of A.I. and the concept of Ihsan, this plenary intends to demystify A.I. and an attempt to harmonize this leap-of-faith tool, into a tool for the faithful International Journal of Human and Health Sciences Supplementary Issue: 2019 Page: 9